2000
DOI: 10.1074/jbc.275.14.9963
|View full text |Cite
|
Sign up to set email alerts
|

Purified NS2B/NS3 Serine Protease of Dengue Virus Type 2 Exhibits Cofactor NS2B Dependence for Cleavage of Substrates with Dibasic Amino Acids in Vitro

Abstract: Dengue virus type 2 NS3, a multifunctional protein, has a serine protease domain (NS3pro) that requires the conserved hydrophilic domain of NS2B for protease activity in cleavage of the polyprotein precursor at sites following two basic amino acids. In this study, we report the expression of the NS2B-NS3pro precursor in Escherichia coli as a fusion protein with a histidine tag at the N terminus. The precursor was purified from insoluble inclusion bodies by Ni 2؉ affinity and gel filtration chromatography under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
283
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(296 citation statements)
references
References 57 publications
12
283
0
1
Order By: Relevance
“…The flanking hydrophobic residues of NS2B are likely to function by promoting association between the protease complex and infected cell membranes (17). The essential nature of the central hydrophilic domain for proteolytic activity has been recently confirmed in vitro with Escherichia coli expressed and purified recombinant NS3pro complexed with this NS2B co-factor domain (18).…”
mentioning
confidence: 95%
“…The flanking hydrophobic residues of NS2B are likely to function by promoting association between the protease complex and infected cell membranes (17). The essential nature of the central hydrophilic domain for proteolytic activity has been recently confirmed in vitro with Escherichia coli expressed and purified recombinant NS3pro complexed with this NS2B co-factor domain (18).…”
mentioning
confidence: 95%
“…Previous studies have shown that NS3 contains two functional domains: a serine protease at the N-terminus and an RNA helicase at the C-terminus [12][13][14] . NS2B is an essential element that acts as a co-factor to greatly enhance the activity of NS3 by 3300-to 6600-fold [15,16] . As a viral protease complex, NS2B/ NS3 is mainly in charge of cleaving the viral poly-protein precursor to generate structural proteins and nonstructural proteins, and the disruption of NS2B/NS3 protease function distinctly inhibits viral replication [17] .…”
Section: Introductionmentioning
confidence: 99%
“…In the past, successful structure-based drug development against NS3pro of the hepatitis C virus (HCV) has generated a series of United States Food and Drug Administration (FDA)-approved inhibitors with potent efficacy for viral eradication [6]. Flavivirus NS3pro exists predominantly in an inactive state; however, upon association with the NS2B viral protein, its enzymatic activity increases by 3 300-6 600-fold [7]. The recent structure of ZIKV NS2B-NS3pro in complex with a boronate inhibitor has provided some important insights for drug design [8].…”
mentioning
confidence: 99%